2002
DOI: 10.1063/1.1485124
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of strain relaxation in InGaAsN and InGaAs thin films

Abstract: We compare the strain relaxation of In0.08Ga0.92As and In0.12Ga0.88As0.99N0.01 epitaxial thin films grown on GaAs (001) by elemental-source molecular-beam epitaxy. The epilayers we studied were essentially identical in their compressive lattice mismatch (0.62±0.02%), and thickness (600 nm). The strain state of the samples was determined by in situ substrate curvature monitoring, and by ex situ x-ray diffraction and plan-view transmission electron microscopy. We observe a slower rate of strain relaxation, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…[12][13][14] The morphology at various points of the strain evolution was also examined. The induced strain thus calculated is th = 0.26 ϫ 10 −3 , which corresponds to an induced tensile stress th = 0.03 GPa, and is in reasonable agreement with the measured stress.…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14] The morphology at various points of the strain evolution was also examined. The induced strain thus calculated is th = 0.26 ϫ 10 −3 , which corresponds to an induced tensile stress th = 0.03 GPa, and is in reasonable agreement with the measured stress.…”
Section: Resultsmentioning
confidence: 99%
“…4 The epitaxial growth of dilute nitride layers, such as GaAsN and GaPN, is particularly challenging under conditions of lattice mismatch since these alloys show plastic properties which are drastically different from those of conventional ternary alloys such as GaAsP or GaInAs. [5][6][7][8] Consequently, the strain relaxation is not well described by equilibrium models, such as the classical Matthews and Blakeslee model, 9 and high-quality strain-relaxed layers are difficult to obtain. [5][6][7][8] Consequently, the strain relaxation is not well described by equilibrium models, such as the classical Matthews and Blakeslee model, 9 and high-quality strain-relaxed layers are difficult to obtain.…”
mentioning
confidence: 92%
“…5 It has been shown that already small concentrations of nitrogen may lead to considerable alloy hardening making the formation and glide of dislocations difficult. 7,8,10,11 While the effect of hardening of dilute nitrides has mainly been recognized as a problem, we show that this phenomenon can actually be used as a tool for controlling defect formation and strain relaxation in lattice mismatched heteroepitaxy. 7,8,10,11 While the effect of hardening of dilute nitrides has mainly been recognized as a problem, we show that this phenomenon can actually be used as a tool for controlling defect formation and strain relaxation in lattice mismatched heteroepitaxy.…”
mentioning
confidence: 99%
“…Grazing-incidence X-ray diffraction (GIXD) is a powerful method of measuring strain and delineating interface structures in a variety of sample systems, such as quantum dots, quantum wires, nano-particles, thin-films, and multi-layer superlattices [1][2][3][4][5][6][7][8][9][10][11][12][13]. However, grazing-incidence X-rays penetrate only several hundred angstroms into the sample due to total reflection effect.…”
Section: Introductionmentioning
confidence: 99%